Sexual assault prevention in the military: Key issues and recommendations. Issue 3 (4th May 2018) - Gidycz, Christine A.; Wyatt, Joel; Galbreath, Nathan W.; Axelrad, Stephen H.; McCone, Dave R.
ABSTRACT: Data suggests that sexual assault and harassment continue to be significant concerns within the U.S. military. Given such findings, the Department of Defense and the component military services have recently developed several initiatives aimed at preventing sexual violence within their ranks. A number of these programming efforts are modeled after prevention initiatives in other communities such as college campuses. In this article, the authors discuss major issues that are important for the military as they move forward to augment their sexual assault prevention efforts. Previous prevention work both within and outside of the military will be discussed in the context of the reviewed issues. The article concludes with a list of recommendations.